The Imperative of Social Justice on the Insolvency and Workers' Wage - Nuryanto, Ahmad Dwi; Kusumaningtyas, Reza Octavia; Habibullo, Bukhadyrov (Lembaga Contrarius Indonesia, 2024)
Several laws and regulations in Indonesia govern the wage rights of workers in insolvent companies. However, there is a lack of coordination among these regulations, which affects their effectiveness. This research examines the impact of bankruptcy on worker protection within the framework of social justice principles. Utilizing normative legal research with a conceptual approach, the study reveals that bankruptcy often disadvantages employees, who are frequently placed at the end of the creditor hierarchy during the distribution of bankrupt assets. Despite the existence of various laws designed to protect laborers' rights, there is considerable overlap and inconsistency among them. Therefore, it is essential to clarify the status of employees in bankrupt companies and harmonize relevant regulations to ensure fair compensation for workers. The research also includes comparative examples from different countries. The prioritization of employee claims in insolvency cases varies according to each country's legal framework and social security system. For instance, Germany, the United Kingdom, and France exhibit significant differences in their approaches to pay priorities. These differences highlight the complex interaction between statutory priorities, social security systems, and cultural attitudes towards labor rights, which collectively influence the respective pay priority frameworks of these countries. The findings underscore the need to ensure equitable treatment of employees within global economic systems while balancing competitiveness with labor rights.